SIMULATION OF A SOLAR DRIVEN AIR CONDITIONING SYSTEM FOR A HOUSE IN DRY AND HOT CLIMATE OF ALGERIA - DJELLOUL, A.; DRAOUI, B.; MOUMMI, N. (Courrier du Savoir; Vol. 15 (2013): Courrier du Savoir, 2014)
Solar cooling technology is environmentally friendly and contributes to a significant decrease of the CO2 emissions which cause the green house effect .Currently, most of the solar cooling systems commonly used are the hot water driven lithium bromide absorption chillers. According to the operating temperature of driving thermal source, single – effect Li Br/H2O absorption chillers have the advantage of being powered by ordinary flat-plate or evacuated tubular solar collectors available in the market. The main objective of this work is to develop a computational model that allows the simulation of an hourly basis for an absorption refrigeration - single - effect used the LiBr/H2O as solution working fluid- system assisted by solar energy and natural gas as auxiliary fuel coupled with the residential building located in the hot and dry climate of Algeria. This model will be developed using the dynamic simulation program TRNSYS, considering three specifics areas of work: determination of the cooling loads for a building, implementation of the computational model for the absorption refrigeration system and the parametric optimization of components, which will make possible an approach to optimal sizing of the solar absorption system. The results of the simulation of the absorption chiller indicate that an area of 28 m2 of flat plat collectors with an inclination of 35° and 800 L for hot storage tank provides an annual solar fraction of 80% and a thermal performance coefficient COP of 0.73, getting to cover demand of air conditioning in a house of 120 m2 located in Biskra (Algeria).